Assessment of an intervention experience using appropriate technologies in Santiago del Estero (Argentina) (2018)
In previous discussions about technological change, “Socially Appropriate Technologies” emerged as one of the alternatives to the modernizing model of technology transfer that prevailed for many years in Latino America. However, despite the time elapsed since its conceptual creation, it is not easy to find studies valuing interventions carried out with this type of approach. This paper pretends to approximate the subject by analyzing a technology transfer experience in the usage of goat manure as a fertilizer for household crops in Santiago del Estero (Argentina). Despite having a priori socially appropriate design, technology was not replicated by all the experimenters. A quantitative and qualitative two-stage approach was used to address it. The first approach explores structure variables of each experimenter and correlated them with the times that this experimenter repeated the practice. The second, analyzes the farm operation, through case studies. The results indicate that a particular farm structure did not guarantee a result in terms of appropriation of a Socially Appropriate Technology, and that the operation of the production system and the survival strategy (or peasant strategy) of each family gave the farm a dynamic that often is decisive in adopting the proposal. In addition, at least for the current experience was not enough to design technology using locally controlled resources, nor was it appropriate to present a unique technological proposal for all of the experimenters. The multiple adjustments and technological substitutions used by farmers show that it would be interesting to work with the local innovation processes that take place in the territory.